If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5c + -2c + 12 = 5 Reorder the terms: 12 + -5c + -2c = 5 Combine like terms: -5c + -2c = -7c 12 + -7c = 5 Solving 12 + -7c = 5 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -7c = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -7c = 5 + -12 -7c = 5 + -12 Combine like terms: 5 + -12 = -7 -7c = -7 Divide each side by '-7'. c = 1 Simplifying c = 1
| s^2+4s+25=0 | | 3d=4 | | 2(4x+2)+2(2x)=2(4x)+2(4x) | | -3/4=m/22 | | 9/2=k/25 | | 4.14-3(2.6x-5)=6.9x-(x-1) | | 8x+80=180 | | 6-3b=-18 | | 6x-2=7x | | 45g*37+6=58(22+7) | | -.5x+1.5=.5(3-x) | | x^3-10x^2+35x-27=0 | | p-6= | | 0.6(y+3)=5.4 | | 3x=101 | | 3a+12=21 | | 0.4x-y=4+3y | | 0.3(0.1x+0.7)=-0.3 | | 167-2x=25x+20 | | 12+4x=2+3x | | 12z-(4z+6)=8z | | 9(x+2)=27 | | -2x+4=2(4x-3)3(-8+4x) | | 3x-1+1=1+1 | | 0.1x^2+1.6x+1.5=0 | | 2t+3=-9 | | -3x-1+1= | | -7(x+3)=-2(x+3)-15x | | f(3)=x^2+7 | | -1=9-0.66666666667x | | 8x+7x=0 | | 2(4-2y)=3y |